Autosomal recessive nonsyndromic hearing impairment in two Finnish families due to the population enriched CABP2 c.637+1G>T variant. Issue 3 (11th February 2022) - Bharadwaj, Thashi; Schrauwen, Isabelle; Acharya, Anushree; Nouel‐Saied, Liz M.; Väisänen, Marja‐Leena; Kraatari, Minna; Rahikkala, Elisa; Jarvela, Irma; Kotimäki, Jouko; Leal, Suzanne M.
Abstract: Background: The genetic architecture of hearing impairment in Finland is largely unknown. Here, we investigated two Finnish families with autosomal recessive nonsyndromic symmetrical moderate‐to‐severe hearing impairment. Methods: Exome and custom capture next‐generation sequencing were used to detect the underlying cause of hearing impairment. Results: In both Finnish families, we identified a homozygous pathogenic splice site variant c.637+1G>T in CAPB2 that is known to cause autosomal recessive nonsyndromic hearing impairment. Four CABP2 variants have been reported to underlie autosomal recessive nonsyndromic hearing impairment in eight families from Iran, Turkey, Pakistan, Italy, and Denmark. Of these variants, the pathogenic splice site variant c.637+1G>T is the most prevalent. The c.637+1G>T variant is enriched in the Finnish population, which has undergone multiple bottlenecks that can lead to the higher frequency of certain variants including those involved in disease. Conclusion: We report two Finnish families with hearing impairment due to the CABP2  splice site variant c.637+1G>T. Abstract : The genetic architecture of hearing impairment in Finland is largely unknown. Here, we investigated two Finnish families with autosomal recessive nonsyndromic symmetrical moderate‐to‐severe hearing impairment. Exome and custom capture next‐generation sequencing were used to detect the underlying cause of hearing impairment. In both Finnish families, we identified a homozygous pathogenic splice site variant c.637+1G>T in CAPB2 that is known to cause autosomal recessive nonsyndromic hearing impairment.